Cooperation of arbuscular mycorrhizal fungi and bacteria to facilitate the host plant growth dependent on soil pH - Feng, Zengwei; Liu, Xiaodi; Qin, Yongqiang; Feng, Guangda; Zhou, Yang; Zhu, Honghui; Yao, Qing (Frontiers in Microbiology, 2023)
Almost all plants grow well in their native soils. We hypothesized that soil microbes promote the growth of their hosts in native soils by the example of soil pH. Here, bahiagrass (Paspalum notatum Flugge) indigenous to subtropical soils was grown in the native soil (the original pH = 4.85) or in pH-adjusted soils with sulfur (pH = 3.14 or 3.34) or calcium hydroxide (pH = 6.85, 8.34, 8.52 or 8.59). Plant growth, soil chemical property, and microbial community composition were characterized to reveal the microbial taxa promoting plant growth in the native soil. Results showed that shoot biomass was the highest in the native soil, while both the decrease and increase in the soil pH reduced the biomass. Compared with other soil chemical properties, soil pH was the top edaphic factor contributing to the differentiation in arbuscular mycorrhizal (AM) fungal and bacterial communities. The top 3 most abundant AM fungal OTUs belonged to Glomus, Claroideoglomus, and Gigaspora, while the top 3 most abundant bacterial OTUs belonged to Clostridiales, Sphingomonas, and Acidothermus, respectively. Regression analyses between microbial abundances and shoot biomass revealed that the most abundant Gigaspora sp. and Sphingomonas sp. were the most promotive fungal and bacterial OTUs, respectively. The application of these two isolates to bahiagrass solely or in combination indicated that Gigaspora sp. was more promotive than Sphingomonas sp. across the soil pH gradient, and they positively interacted to enhance biomass only in the native soil. We demonstrate that microbes cooperate to facilitate host plants to grow well in their native soils with the original pH. Meanwhile, a high-throughput sequencing-guided pipeline to efficiently screen for beneficial microbes is established.